Mathematical Derivative for Solving Constrained Optimization in Utility Functions in Economics - Yaqin, Nurul (APPLICATION: Applied science in Learning Research, 2025)
Mathematics is an important assistant tool used by other disciplines to obtain quantitative result in the problem-solving process. The optimum problem is one of the exciting problems that will be the object of our discussion in this article. The main idea of this article is to show how Substitution and Lagrange multiplier methods can solve a constrained optimization problem in economics. In this article, author will study and show how far and easy to solve economic optimum problems using mathematical formulas. Then, with an example of daily problem in economics, the author hopes that it will provide an overview for economic practitioners about how potential mathematical concepts can help them. And it will also be understood that how important it is, to approach and simplify a real-world problem in economics with a mathematical model so that mathematical formulas can be applied to appropriately solve economic problems with the best or optimal results. And eventually, it will also show us that economics in fact are increasingly mathematical.